(untitled) (Research, Society and Development, 2022)
Objective: To assess, with a systematic review (SR) with meta-analysis, the occurrence of genotoxic effects on the oral epithelium after exposure to tooth bleaching agents. Material and methods: This review was performed according to the PRISMA protocols. To identify relevant studies, a systematic search was performed in the following electronic databases: PubMed, Scopus, Embase, LILACS, and Google Scholar. The research question was "Can tooth bleaching agents cause genotoxicity in the oral epithelium?”. The treatment effects were defined as the standardized mean difference (SMD) and 95% confidence intervals (CI) were established. Results: 154 studies were selected and, after screening titles and abstracts, seven full-text manuscripts were assessed for eligibility, of which four studies were included in the meta-analysis. There were no statistically significant differences in the frequency of micronuclei before and after exposure (SMD= -0.14, 95% CI, 0.98 to 0.60, p=0.74), with a Tau2 index = 1.00; Chi2 = 70.20; p-value <0.00001; and I² of 93%, indicating high heterogeneity among the studies. Conclusion: Considering the limitations of the present SR, tooth bleaching agents do not lead to genotoxic damage in the oral epithelium but with a small effect and low level of evidence. In this way, the use of tooth bleaching agents is safe on the oral mucosa but randomized clinical trials that are more standardized in all stages are required to produce more robust evidence.